2022
DOI: 10.1038/s41598-022-13368-x
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of radiosensitization induced by gold and iron oxide nanoparticles in human glioblastoma cells irradiated by 6 MV photons

Abstract: In this work, an intercomparison of sensitization effects produced by gold (GNP) and dextran-coated iron oxide (SPION-DX) nanoparticles in M059J and U87 human glioblastoma cells was performed using 6 MV-photons. Three variables were mapped: the nanoparticle material, treatment concentration, and cell radiosensitivity. For U87, GNP treatments resulted in high sensitization enhancement ratios (SER$$_{10\%}$$ 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…• At similar metal-mass uptake Au NPs showed higher enhancement than SPION-DX [237] MOFs: Hf-DBA, Hf-TCPP, Ti/Zr-PCN-415, Ti-MIL-125…”
Section: In Vitro MV Photonsmentioning
confidence: 97%
“…• At similar metal-mass uptake Au NPs showed higher enhancement than SPION-DX [237] MOFs: Hf-DBA, Hf-TCPP, Ti/Zr-PCN-415, Ti-MIL-125…”
Section: In Vitro MV Photonsmentioning
confidence: 97%
“…Owing to a higher attenuation coefficient, the radiosensitization strategies have mainly focused on high atomic number nanoparticles (High Z NPs) [ 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ]. However, some emerging studies used nanomaterials that have the ability to improve RT efficiency through other mechanisms such as SPION.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Results demonstrated that SIONPs potentially improve the radio-sensitivity of breast cancer [66]. Guerra et al [67] studied the radio-sensitization effects produced by gold and dextran-coated superparamagnetic iron oxide nanoparticles (SPION-DX) in M059J and U87 human glioblastoma cell lines irradiated by 6 MV photons beam. For U87 cells, SPION-DX nanoparticles with a core diameter of 21.1 nm showed a maximum sensitization enhancement ratio (SER10%) = 1.61 in the group exposed to 50 µg/mL of nanoparticles.…”
Section: Iron-based Nanoparticlesmentioning
confidence: 99%